THE WATER SECURITY MANAGEMENT AND ITS INFLUENCE TOWARDS INTER-STATE CONFLICT IN THE MIDDLE EAST REGION - Umam, M. Yudha Hawaril; Kusuma, Bayu Mitra Adhyatma (JURNAL MANAJEMEN DAKWAH, 2015)
Water is an irreplaceable element in the human life. Water security was always pursued by each country to ensure the prosperity of its people. But in fact, more than a third of the world’s population needs of fresh water are not fulfilled, both for drinking and sanitation. So that’s why water security management is urgent to implement. That problem was happened in the Middle East region until today. As we know that most of the Middle East region is composed from the barren desert. Although under the desert there are abundant of oil, but the water is a problem for most of the Middle East region. Middle East region needs a constant water supply approximately 127.5 billion cubic meters per year. Such conditions involve in water scarcity and inter-state conflicts caused by the water. Conflict in the struggle for water resources is difficult to avoid because the water needs in the Middle East region is bigger than the water availability. Those inter-state conflict involving various countries including Israel, Egypt, Jordan, Palestine, Lebanon, and Syria. Appropriate and equitable solutions should be formulated and implemented, such as making water management agreement which must be agreed by all countries. Because if not addressed, the seizure of water resources can be lead to high tension, conflict, or even war in the Middle East region. To elaborate the data, this research uses qualitative method, descriptive analysis approach, and emphasize on the literature study. Keywords: Water Security Management, Inter-State Conflict, Middle East